Process Analytics Workbench (PAW) - Wang, Weixin; Amann, Eric; Matzner, Martin; Delfmann, Patrick (ICPM Doctoral Consortium and Demo Track 2024, 2024)
The Process Analytics Workbench (PAW) is a comprehensive tool to streamline Predictive Process Monitoring (PPM) activities. It integrates functionalities like synthetic event log generation, model training, and prediction evaluation within a micro-service architecture, enabling agile and efficient experimentation.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Event log; Predictive Process Monitoring; Process model; Rapid experimentation; Simulation